LINGUISTIC FEATURES OF ECONOMIC TERMS AND THE METHODOLOGY OF THEIR TEACHING - Djamalutdinova Barno Ramizitdinovna (Modern American Journals, 2025)
This article comprehensively covers innovative approaches to the technique of teaching economic terms. Since the traditional methods of teaching do not fully meet the modern requirements of education, the significance of using creative and interactive teaching methods in the learning process is becoming increasingly important. In this regard, such methods as contextual learning, morphological analysis, phraseological and collocational learning, analogy and contrast, and dialogue and role-play contribute not only to the assimilation of economic terms, but also to their effective application in real economic processes. Global experience shows that when innovative methods are used in teaching economic language, students have the opportunity to independently analyze, critical thinking, and deeply master linguistic competence.
Keywords: Economic terms, linguistic features, innovative methodology, interactive education, economic language teaching, contextual teaching, gamification, case study, artificial intelligence